The Relationship between Health Status and Health Behaviors of the in Ban Pong Din, Pa Miang Subdistrict, Doi Saket District, Chiang Mai Province - Chandeekaewchakool, Sarinyaporn; Phuangngoenmak, Sinee; Rattanamahamaneekorn, Opart; Buankham, Areerat (Journal of Nursing and Public Health Research, 2025)
This cross-sectional research aimed at examining the relationship between health status and health behaviors among residents of Ban Pong Din. The sample consisted of 109 individuals aged 15 years and older who participated in a health screening. Participants were selected using purposive sampling. Data collection tools included a personal information record form, a health status questionnaire, and a health behavior questionnaire. Data were analyzed using descriptive statistics and Pearson's correlation coefficient. The results revealed that most participants had an overall low level of health behaviors (Mean = 1.05, S.D. = 0.25). Body Mass Index (BMI) was found to have a low positive correlation with health-risk behaviors, with statistical significance (r = 0.36, p-value < 0.01). Blood pressure showed a low negative correlation with both health-promoting behaviors and health-risk behaviors (r = 0.25, p-value < 0.01). Additionally, mental health status had a low positive correlation with health-promoting behaviors (r = 0.20, p-value < 0.05). Based on the findings, nurses and staff at sub-district health promoting hospitals can use this information to plan health promotion activities aimed at modifying community members’ behaviors, with the goal of preventing the onset of new chronic diseases. Moreover, these activities may encourage individuals with chronic conditions to adopt healthier behaviors, thereby reducing the risk of disease complications.